The Relationship Between Spiritual/Religious Engagement and Affective College Outcomes: An Analysis by Academic Disciplines - Kim, Young K.; Carter, Jennifer L.; Rennick, Liz A.; Fisher, Daniel (Journal of Interdisciplinary Studies in Education, 2023)
Using a state-wide college student dataset, this study examines how the level of college students’ spiritual/religious engagement varies by academic disciplines and how the impact of such engagement on affective college outcomes varies across different academic disciplines. Findings show that students majoring in soft-applied-life disciplines (e.g., education, public health, and counseling) are more likely to engage in spiritual/religious activities whereas those who major in the hard-applied-life disciplines (e.g., agriculture, animal sciences, nursing) and hard-applied-nonlife disciplines (e.g., engineering, computer sciences, pharmacy) are less likely to do so. Our findings also suggest that students in some academic disciplines benefit more or less than their counterparts in other academic disciplines.